Prenatal management of congenital diaphragmatic hernia. Issue 6 (December 2022) - Danzer, Enrico; Rintoul, Natalie E.; van Meurs, Krisa P.; Deprest, Jan
Abstract: Recently, two randomized controlled, prospective trials, the Tracheal Occlusion to Accelerate Lung Growth (TOTAL) trials, reported the outcomes on fetal endoluminal tracheal occlusion (FETO) for isolated left congenital diaphragmatic hernia (CDH). FETO significantly improved outcomes for severe hypoplasia. The effect in moderate cases, where the balloon was inserted later in pregnancy, did not reach significance. In a pooled analysis investigating the effect of the heterogeneity of the treatment effect by the time point of occlusion and severity, the difference may be explained by a difference in the duration of occlusion. Nevertheless, FETO carries a significant risk of preterm birth. The primary objective of this review is to provide an overview of the rationale for fetal intervention in CDH and the results of the randomized trials. The secondary objective is to discuss the technical aspects of FETO. Finally, recent developments of potential alternative fetal approaches will be highlighted. Highlights: Congenital diaphragmatic hernia (CDH) is a prenatally diagnosed malformation that is associated with significant neonatal mortality and long-term morbidities. Following prenatal diagnosis, families should receive individualized counseling regarding mid gestational management options based on prenatal and associated prognostic measures. The randomized trials of Tracheal Occlusion to Accelerate Lung Growth (TOTAL) provided level one evidence that fetoscopic endoluminal tracheal occlusion (FETO) improves survival in selected cases of isolated CDH. Fetal surgical intervention is however associated with maternal and fetal risks. Continued evaluation of children enrolled in the TOTAL trials will be necessary to evaluate the long-term impact of fetal intervention and contribution of prematurity to morbidity outcomes. Prior to widespread implementation of FETO to less experienced centers, prospective registration of new cases treated with FETO at high volume centers with experience in both fetal therapy and CDH care are needed to further increase our understanding of the effects FETO on the natural history of CDH. Development of a pulmonary hypoplasia "biophysical profile" that incorporates measures of both lung size and pulmonary vascular function is needed to improve risk stratification for prenatal counseling and selection for fetal intervention. Technical refinements and investigation of additional, but preferentially alternative, non-surgical prenatal management options, such as transplacental pharmacologic modulation of lung development or cell-based and tissue engineering therapy may improve outcomes and decrease the risk to the mother and fetus.